URBAN SLANG: THE LANGUAGE OF IDENTITY, COMMUNITY, AND CULTURAL EXPRESSION AMONG YOUTH - Togayev , Sarvar; Erkinov , Khurshid (Scientific practical conference, 2026)
Urban Slang, a dynamic and multifaceted aspect of youth culture, acts both by communicative tool and from a vehicle for the formation of identity among young people. Defined as an informal and non-standard language often rooted in the community and specific subcultures, urban jargon emerges from a variety of linguistic influences, including African American vernacular English (Aave), hip-hop culture and Internet subcultures. Its prevalent use in daily communication illustrates not only the adaptability of language, but also the social dynamics in which it operates. As an expression of cultural identity, urban jargon reflects the experiences of youth, capturing their prospects on identity, belonging and social realities in a society in constant evolution (Normurodovna, 2024).